Separation of glycosidic catiomers by TWIM‐MS using CO2 as a drift gas. (3rd February 2015) - Bataglion, Giovana A.; Souza, Gustavo Henrique Martins Ferreira; Heerdt, Gabriel; Morgon, Nelson H.; Dutra, José Diogo Lisboa; Freire, Ricardo Oliveira; Eberlin, Marcos N.; Tata, Alessandra
Abstract : Traveling wave ion mobility mass spectrometry (TWIM‐MS) is shown to be able to separate and characterize several isomeric forms of diterpene glycosides stevioside (Stv) and rebaudioside A (RebA) that are cationized by Na + and K + at different sites. Determination and characterization of these coexisting isomeric species, herein termed catiomers, arising from cationization at different and highly competitive coordinating sites, is particularly challenging for glycosides. To achieve this goal, the advantage of using CO2 as a more massive and polarizable drift gas, over N2, was demonstrated. Post‐TWIM‐MS/MS experiments were used to confirm the separation. Optimization of the possible geometries and cross‐sectional calculations for mobility peak assignments were also performed. Copyright © 2015 John Wiley & Sons, Ltd.